Рекогносцировка местонахождения Меджибож в 2008—2009 гг. - Степанчук, В.Н.; Рыжов, С.Н. (Археологічні дослідження в Україні, 2010)
Medzhybizh paleontological site has been known for more than 100 years. In the 1950s, the first objects presumably processed by the human were found here. At the end of the 1990s and the beginning of the 2000s new evidence appeared about the existence of materials in horizons of Mindel and Ris age (approximately 400 thousand BP). In 2008 and 2009, reconnaissance works were conducted at the site which assured the archaeological status of the monument and undoubted perspectiveness of its study.